2020
DOI: 10.1371/journal.pone.0242578
|View full text |Cite
|
Sign up to set email alerts
|

Using bodily postures to reduce anxiety and improve interoception: A comparison between powerful and neutral poses

Abstract: Background Previous research has shown that anxiety syndromes are highly prevalent among university students. Effective treatments are needed to reduce the burden of anxiety in this population. Powerful postures have been found to impact affective states, as well as interoception (i.e. the ability to perceive inner bodily signals). However, no previous study has compared the effects of powerful- and neutral postures in regards to anxiety and interoceptive ability. Methods The first part of the study measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 96 publications
0
14
0
Order By: Relevance
“…It needs to be noted that our study is the first that investigated IS in the context of a heartbeat perception training. Similarly, Weineck et al (2020b) found increased IAc due to a single session of power posing in healthy women, whereas there was also no change in IS as assessed via confidence ratings and via the Body Perception Questionnaire ( Porges, 1993, 2015 ). The authors argue that interventions targeting individuals’ self-focus might not be directly associated with increases in performance confidence.…”
Section: Discussionmentioning
confidence: 88%
“…It needs to be noted that our study is the first that investigated IS in the context of a heartbeat perception training. Similarly, Weineck et al (2020b) found increased IAc due to a single session of power posing in healthy women, whereas there was also no change in IS as assessed via confidence ratings and via the Body Perception Questionnaire ( Porges, 1993, 2015 ). The authors argue that interventions targeting individuals’ self-focus might not be directly associated with increases in performance confidence.…”
Section: Discussionmentioning
confidence: 88%
“…For example, one study among adults with depression showed that a single session of adopting an upright posture led to acute reductions in anxiety and negative affect, compared with sitting in a neutral position ( Wilkes et al, 2017 ). A more recent two-arm longitudinal study of healthy college students reported that adopting either experimentally prescribed powerful or neutral postures for 2 weeks led to reduced trait anxiety ( Weineck et al, 2020 ). Interestingly, improvements in trait anxiety in both interventions paralleled improvements in interoceptive awareness.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous short-term studies of experimentally induced mood states have also shown that behavior can influence posture ( Oosterwijk et al, 2009 ). Conversely, short-term studies of experimentally manipulated posture have shown that body shapes can affect an individual’s emotional state ( Weineck et al, 2020 ). Adopting a stooped, neutral, or upright posture has been shown to influence persistence ( Riskind, 1983 ), stress ( Kwon and Kim, 2015 ), interoceptive accuracy and feelings of power ( Carney et al, 2010 ; Weineck et al, 2019 , 2021 ) but see Elkjær et al (2020) .…”
Section: Introductionmentioning
confidence: 99%
“…More generally, modulating the body’s position can have a meaningful impact on mood regulation ( Veenstra et al, 2017 ) and plays a part in reducing anticipatory anxiety ( Lipnicki and Byrne, 2008 ; Weineck et al, 2020 ) and mental health in general ( Domingues, 2018 ), moreover, it can improve interoception ( Weineck et al, 2020 ). While many studies use gross postural differences to examine the phenomenon, such as slumped or erect and standing or supine conditions, it is quite possible that smaller changes in the posture might lead to similar benefits, which, given the high levels of performance anxiety and other mental health concerns in this population, might be a valuable tool.…”
Section: Discussionmentioning
confidence: 99%